PENGUATAN STRATEGI SOSIALISASI BERBASIS EVALUASI PENERIMAAN MAHASISWA BARU - Abdullah, Abdul Haris; Tola, Baso (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2025)
The increasingly competitive landscape of student recruitment among higher education institutions in Indonesia, including Islamic State Higher Education Institutions (PTKIN), requires a shift toward evidence-based promotional strategies. This study aims to analyze and strengthen socialization strategies for new student admissions through an evaluative approach based on the theory of higher education marketing. Using an integrative literature review method, this research synthesizes relevant studies, reports, and policy documents published between 2019 and 2025 concerning student recruitment and institutional communication in Islamic higher education. The findings indicate that most PTKIN still employ conventional socialization methods that lack systematic evaluation and data utilization. The absence of integrated data analysis on student admissions has resulted in repetitive, less effective promotional practices. From the marketing perspective, effective socialization should be grounded in value-based and relationship-oriented communication strategies that align with the institution’s identity, academic reputation, and service quality. Furthermore, digital transformation and local cultural adaptation are essential to enhance visibility and engagement with potential students. This review proposes a conceptual model of strengthening socialization strategies based on continuous evaluation cycles—linking data analysis, strategic communication, and institutional collaboration. The study concludes that evaluation-based socialization not only improves recruitment outcomes but also enhances the institutional image and competitiveness of PTKIN as centers of excellence in Islamic higher education.